108 Are There Differences in Stretched Flaccid Penile Length Versus Erectile Penile Length in Men with Erectile Dysfunction?. (1st May 2022) - Martinez, J Flores; Salter, CA; Benfante, N; Schofield, E; Mulhall, JP
ABSTRACT: Introduction: Penile length measurement is an important tool in various clinical scenarios in andrology. It has been suggested that stretched flaccid penile length (SFPL) is an excellent surrogate for erect penile length (EPL). Objective: We aimed to evaluate if the SFPL accurately reflects EPL. Methods: Men with (i) Erectile Dysfunction (ED) without penile curvature (ii) undergoing penile duplex doppler ultrasound (DDUS) (iii) with a rigid erection were analyzed. SFPL and EPL were measured dorsally from the pubic symphysis to the coronal sulcus. Significant discrepancy was defined as a difference ≥1cm between the two measurements. We collected demographic and comorbidity data. Results: 64 men were analyzed with a mean age of 59.4 ± 13.4 years. 37.5% of the patients reported 2 or more comorbidities, 11% had diabetes, 19% obstructive sleep apnea, 29% were current or former smokers, 54% had radical pelvic surgery, and 44% pelvic radiation. Mean SFPL was 10.8 ± 1.9 cm and mean EPL was 11.8 ± 1.8 cm, (p<0.001). 83% had EPL>SFPL. 47% of men had a significant discrepancy between the two measurements. No predictors of discrepancy were identified. Conclusions: In our cohort of men with ED assessed during DDUS, there was a statistically significant difference between SFPL and EPL measurements. In almost half of the cases EPL was significantly longer than SFPL. SFPL is not a reasonable surrogate for erect penile length Disclosure: Work supported by industry: no.